Two cases of retroperitoneal hematoma caused by combination of anticoagulant therapy and 5-fluorouracil - Murase, Tomoya; Minato, Masako; Furutani, Kaori; Tsujikawa, Tetsuya; Morita, Naomi; Nishitani, Hiromu; Otsuka, Hideki; Furutani, Syunnsuke; Yoneda, Kazuhide; Tagashira, Hiroshi; Kashihara, Kennichi (The Journal of Medical Investigation, 2005)
We reported two cases of retroperitoneal hematoma in patients who received a combination of anticoagulant therapy and 5-fluorouracil (5-FU). We should be aware of the possible interaction of this combination therapy and monitor prothrombin time (PT) prolongation. CT is useful for evaluation of the disease. J. Med. Invest. 52: 114-117, February, 2005